2015
DOI: 10.1016/j.jacr.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Characteristics on the Availability of Radiology Services at Critical Access Hospitals

Abstract: Total hospital expenditures and network participation are important determinants of whether CAHs provide certain imaging services. Encouraging CAHs' participation in larger systems or networks may facilitate access to highly specialized services in rural and underserved areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…An acute care general hospital can be designated a CAH by Medicare if it (1) is located in a rural area with a State Medicare Rural Hospital Flexibility Program, (2) provides 24-hour emergency care services using on-site or on-call staff members, (3) has no more than 25 inpatient beds, (4) has an average annual length of stay of 96 hours or less, and (5) is located more than 35 miles from the nearest hospital (15 miles in mountainous terrain) or is state certified as a necessary provider. Evidence suggests that CAHs have improved rural access to medical care, including to imaging services [ 23 ]. A recent report on critical access hospitals showed that 95% of CAH have a CT scanner and 83% can perform MRIs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An acute care general hospital can be designated a CAH by Medicare if it (1) is located in a rural area with a State Medicare Rural Hospital Flexibility Program, (2) provides 24-hour emergency care services using on-site or on-call staff members, (3) has no more than 25 inpatient beds, (4) has an average annual length of stay of 96 hours or less, and (5) is located more than 35 miles from the nearest hospital (15 miles in mountainous terrain) or is state certified as a necessary provider. Evidence suggests that CAHs have improved rural access to medical care, including to imaging services [ 23 ]. A recent report on critical access hospitals showed that 95% of CAH have a CT scanner and 83% can perform MRIs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT utilization has been shown to cluster regionally, 6 with rural regions less likely to provide imaging services. 20 Smokers in rural areas are already known to be an at‐risk group for poor LDCT screening. 21 Our results reflect these regional differences, as the median population of VA stations providing higher LDCT rates was about 2× the median population of those that had lower LDCT rates.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we found geographic variations in costs by comparing urban, rural, and critical access hospital status as defined by the CMS [4]. Previous studies have suggested that access to care for advanced imaging is a concern for rural and critical access hospitals [16,17,22], which may be directly attributable to the relatively high cost of purchasing and maintaining advanced imaging modalities in low-utilization areas [26]. Urban-rural discrepancies in the orthopaedic workforce have been noted previously, with fewer orthopaedic surgeons practicing in rural areas of the country which might affect access to quality orthopaedic care in these areas [11].…”
Section: Discussionmentioning
confidence: 99%